What Clients want: Choices between Lawyers' Offerings - Flora Felso; Sander Onderstal; Jo Seldeslachts (Tinbergen Institute, 2014)
We analyze a client's choice of contract in auctions where Dutch law firms compete for routine cases. The distinguishing feature here is that lawyers may submit bids with any fee arrangement they prefer: an hourly rate, a fixed fee or a mixed fee, which is a time-capped fixed fee plus an hourly rate for any additional hours should the case take longer than expected. Furthermore, this format of selling legal services is unusual in that it both forces lawyers to compete directly against each other and allows clients to easily compare these different offers. We empirically estimate a choice model for clients and find robust evidence that hourly rate bids are a client's least-preferred choice. Our findings tentatively contradict lawyers' often made argument that hourly rates are in a client's best interest.
Keywords: C25; D43; K10; K40; 330; Lawyers' fee arrangements; clients' choices; discrete choice models